1987
DOI: 10.1111/j.1440-1754.1987.tb00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of late presentation neonatal oesophageal atresia with distal tracheo‐oesophageal fistula and significant pulmonary complications

Abstract: The successful management of a neonate presenting with oesophageal atresia and a distal tracheo‐oesophageal fistula on the twelfth day of life is described. This case is the most delayed diagnosis associated with survival known to have been reported. There were significant pulmonary complications at presentation and initial treatment was by gastrostomy under local anaesthesia, followed by a delayed primary repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Our study showed that delayed diagnosis of an OA occurred in up to 27.5% of patients referred to peadiatric tertiary care centres and delay in diagnosis significantly decreased the survival rates. There have been only four reported cases of neonates diagnosed as OA after the first week of life in the literature . In our study, two patients were admitted to the hospital after 7 days of life and had successful outcomes following the surgery.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Our study showed that delayed diagnosis of an OA occurred in up to 27.5% of patients referred to peadiatric tertiary care centres and delay in diagnosis significantly decreased the survival rates. There have been only four reported cases of neonates diagnosed as OA after the first week of life in the literature . In our study, two patients were admitted to the hospital after 7 days of life and had successful outcomes following the surgery.…”
Section: Discussionmentioning
confidence: 80%
“…There have been only four reported cases of neonates diagnosed as OA after the first week of life in the literature. [11][12][13][14] In our study, two patients were admitted to the hospital after 7 days of life and had successful outcomes following the surgery. Gender, type of delivery and type of OA did not lead clinicians to make the diagnosis earlier.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a very few reports of babies presenting for the first time after 1 week of life [3][4][5]. To the best of our knowledge, this is only the fourth reported case where a baby has presented with EA for the first time after the first week of life and has had a successful outcome.…”
mentioning
confidence: 97%
“…However, issues related to public health services in third world countries like home deliveries, long distances between patients and health care centres or even the unawareness of the condition amongst primary treating medical personnel may contribute to the late presentation. There are isolated case reports of neonates with EA with TEF who presented late and survived after surgery [8,9]. Missing the diagnosis at birth and late presentation to tertiary care centre are the important factors that affect survival.…”
Section: Introductionmentioning
confidence: 99%